Platelet rich plasma: a newer modality of cervical erosion treatment - Makhija, Nishi; Jain, Reema (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Cervical erosion is a condition in which squamous epithelium of the vaginal aspect of cervix is replaced by columnar epithelium. Some of the common causes of cervical erosion are poor hygiene, trauma, excessive use of chemicals, infection, malnutrition, low immunity, multiple partners and early age of sexual activity. The common clinical symptoms are mucoid discharge per vaginum, post coital bleeding, lower abdominal pain, low backache and deep dyspareunia. Asymptomatic erosions usually heal on their own, but symptomatic erosions need to be treated. Antibiotics and anti-inflammatory agents are used as the first line of treatment. Cryotherapy is a commonly used treatment modality which causes controlled destruction of tissue by freezing. Another method which holds promise is Carbon dioxide Laser. It works by ablation or vaporisation of abnormal cells and has better precision as well as insignificant pain post procedure. Chemical cautery with silver nitrate stick is also an easy and cheap method of treatment. Platelet rich plasma is a newer modality in which platelet derived growth factors help in tissue healing and epithelisation. It does away with the troublesome side effect of watery discharge post treatment, which is known after all other treatment modalities.